2020
DOI: 10.1029/2020ea001091
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐Annual and Interannual Dynamics of Evaporation Over Western Lake Erie

Abstract: Evaporation (E) is a critical component of the water and energy budget in lake systems yet is challenging to quantify directly and continuously. We examined the magnitude and changes of E and its drivers over Lake Erie-the shallowest and most southern lake of the Laurentian Great Lakes. We deployed two eddy-covariance tower sites in the western Lake Erie Basin-one located nearshore (CB) and one offshore (LI)-from September 2011 through May 2016. Monthly E varied from 5 to 120 mm, with maximum E occurring in Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…The EC measurement period (May-September) was around the turning point in July that led to the weak correlation. Nevertheless, a clear and strong relationship can be established between the two variables for the shallow Lake Balaton similar to other lake studies [14,46,48]. In other words, the available energy (which is driven by SWin) plays a crucial role in the intraannual variability of LE.…”
Section: Hysteresis Behavior Of Evaporation and Its Transfer Coeffici...supporting
confidence: 84%
“…The EC measurement period (May-September) was around the turning point in July that led to the weak correlation. Nevertheless, a clear and strong relationship can be established between the two variables for the shallow Lake Balaton similar to other lake studies [14,46,48]. In other words, the available energy (which is driven by SWin) plays a crucial role in the intraannual variability of LE.…”
Section: Hysteresis Behavior Of Evaporation and Its Transfer Coeffici...supporting
confidence: 84%
“…The maximum LE was about one month to three months lag behind the maximum R n over Erhai Lake. For large and deep lakes with the high heat capacity of lake water, a two to five months delay between maximum LE and R n was observed [17,[58][59][60]. The seasonal variation of the heat storage change (∆Q) can be divided into storaging period (∆Q > 0) and releasing period (∆Q < 0).…”
Section: Meteorological Conditions and Surface Energy Budgetmentioning
confidence: 99%
“…Complete observation records of the ice-free season are important since prior work (e.g. Spence et al 2003;Lenters et al 2005;Granger and Hedstrom, 2011;Spence et al 2011;Liu et al 2012;Shao et al 2020;Fournier et al, 2021) has shown significant differences in atmospheric forcing that drive evaporation processes between the warming, cooling, and frozen phases of lakes. Here warming is broadly defined as the spring mixing and stratification period when the atmosphere is generally warmer than the air, cooling is turnover when the lake is warmer than the air, and frozen is the ice-covered period.…”
Section: Introductionmentioning
confidence: 99%